Analisis Ketahanan Mental Atlet Karate dalam Menghadapi Tekanan Latihan dan Kompetisi dalam Perspektif Bimbingan dan Konseling di SMAN 3 Tana Toraja - Kurniawati Winda; Arlis Masora Pasalongan; Senna Darruk Emeng; Angga Arruan Sangga (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Mental resilience is a crucial psychological asset that determines the performance consistency of athletes under competitive and training pressures. This study aims to analyze the mental resilience of karate athletes at SMAN 3 Tana Toraja from the perspective of guidance and counseling. Employing a descriptive qualitative method, data were gathered through in-depth interviews, participatory observation, and documentation involving eight karate athletes and two coaches selected through purposive sampling. Data analysis followed the interactive model of Miles, Huberman, and Saldaña encompassing data condensation, data display, and conclusion drawing. The findings reveal that athletes generally demonstrate moderate to high levels of mental resilience, characterized by adaptive emotional regulation, positive self-talk, and effective coping strategies. Supporting factors include intrinsic motivation, coach social support, peer cohesion, and cumulative competitive experience. Inhibiting factors comprise unmanaged pre-competition anxiety, absence of structured post-defeat psychological recovery, and limited institutional counseling support. From the guidance and counseling perspective, these findings underscore the critical need for integrating psychological skills training into the karate coaching program, including counselor-facilitated group counseling sessions and individual psychological development plans tailored to each athlete.